IMPLEMENTASI SISTEM KEUANGAN DESA TERHADAP PENGELOLAAN KEUANGAN ALOKASI DANA DESA (ADD) - Dara Fitra Sukwani; Dedy Wijaya Kusuma; Nurshadrina Kartika Sari (STIE Mandala Jember, 2021)
Village Fund Allocation (ADD) is one source of rural income which is generally still the main source of income used in the conduct of geverment village. On efforts to oversee the transparency of village financial management, BPKP and the ministry of home affairs developed a village finansial system application in 2015. The purpose of this study is to describe of the result of the evaluation of the village financial syystem on ADD financial management. And can provide goverment of ADD in accordance with the provisions of the legislation. This research used qualitative descriptive approach whit the case study research sites in Rambigundam village, Rambipuji, Jember. The data is collected through observation, interviews, and documentation to get the validity of the data, carriet out technical examination of the validity of the data which is testing the credibility, tranferability, depability, and confirmability. The result showed that the planning stage until the accountability village Allocation Fund stage have well done, but there are same problems of the implementation, they are the lack of participation from people, the lack of participation of Badan Permusyawaran Desa (BPD), and the lack of village Implementation Teams in preparing the report Accountability Village Fund Allocation.